Validation of the Computerized Pediatric Triage Tool, pediaTRI, in the Pediatric Emergency Department of Lenval Children's Hospital in Nice: A Cross-Sectional Observational Study - Antoine Tran; Antoine Tran; Antoine Tran; Petri Valo; Petri Valo; Camille Rouvier; Emmanuel Dos Ramos; Emmanuel Dos Ramos; Emma Freyssinet; Emma Baranton; Olivier Haas; Hervé Haas; et al. (Frontiers in Pediatrics, 2022)
IntroductionA reliable pediatric triage tool is essential for nurses working in pediatric emergency departments to quickly identify children requiring priority care (high-level emergencies) and those who can wait (low-level emergencies). In the absence of a gold standard in France, the objective of our study was to validate our 5-level pediatric triage tool –pediaTRI– against the reference tool: the Pediatric Early Warning Score (PEWS) System.Materials and MethodsWe prospectively included 100,506 children who visited the Pediatric Emergency Department at Lenval Children's Hospital (Nice, France) in 2016 and 2017. The performance of pediaTRI to identify high-level emergencies (severity levels 1 and 2) was evaluated in comparison with a PEWS ≥ 4/9. Data from 2018–19 was used as an independent validation cohort.ResultspediaTRI agreed with the PEWS score for 84,896 of the patients (84.5%): 15.0% (14.8–15.2) of the patients were over-triaged and 0.5% (0.5–0.6) under-triaged compared with the PEWS score. pediaTRI had a sensitivity of 76.4% (74.6–78.2), a specificity of 84.7% (84.4–84.9), and positive and negative likelihood ratios of 5.0 (4.8–5.1) and 0.3 (0.3–0.3), respectively, for the identification of high-level emergencies. However, the positive likelihood ratios were lower for patients presenting with a medical complaint [4.1 (4.0–4.2) v 10.4 (7.9–13.7 for trauma), and for younger children [1.2 (1.1–1.2) from 0 to 28 days, and 1.9 (1.8–2.0) from 28 days to 3 months].ConclusionpediaTRI has a moderate to good validity to triage children in a Pediatric Emergency Department with a tendency to over-triage compared with the PEWS system. Its validity is lower for younger children and for children consulting for a medical complaint.